Duluth Paper - Experiments Illustrating the Descent of the Charge in an Iron Blast-Furnace - Robert H. Richards; Richard W. Lodge (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1888)
A great deal of speculation, as well as actual experiment, has been devoted to ascertaining the changes in the materials (luring their descent in an iron blast-furnace, affecting (1) the chemical constitution, (2) the mechanical condition, and (3) the arrangement of the materials. With a view to throw some light upon the third question, we constructed a model and tried experiments which are here described. Our model is a vertical section of a furnace, with the lines of the Edgar Thomson furnace D of 1885 for the use of which we arc indebted to Mr. Gayley. The model is 40 inches high, and made to scale (1/2 inch equals 1 foot), and the horizontal section of the space through which the charge falls at any point in the descent is 11/2 in. x d, d being the diameter of the furnace at that place. We are unable to say just where the idea of making this model came from ; perhaps, partly from The Principles of the Manufacture of Iron, and Steel, 1884, I. Lowthian Bell, p. 124 ; partly, also, from